Memanfaatkan Internet of Aquaculture dalam Meningkatkan Kualitas Produksi pada Kelompok Pembudidaya Ikan Koi di Blitar - Dany Primanita Primanita Kartikasari; Adhitya Bhawiyuga; Yuni Kilawati; Yunita Maimunah; Adharul Muttaqin (Journal of Innovation and Applied Technology, 2021)
Koi fish farming is growing because of the stable selling value and the number of fans. One area that is geographically suitable for developing Koi fish farming is Blitar. The production of Koi fish produced by cultivators in Blitar is known to have quality that is not inferior to Koi from other countries so that consumers are spread all over the world. This disease is thought to originate from the decline in environmental quality that is not handled properly, causing a decrease in the Koi fish's immune system. The purpose of this activity is to provide education and assistance on efforts to prevent mortality that occurs in Koi fish through the provision of natural immunostimulants and water quality control using internet-based tools to Koi fish farmers in Blitar. the use of materials and tools as well as the provision of immunostimulant materials and internet-based water quality detectors.